Impacts of oyster farms on sediment-associated mercury and methylmercury concentrations and health risks in an estuarine, mangrove forest, Zhanjiang Bay, China - Zhao, Zike; Chen, Chunliang; Feng, Mengqian (Frontiers in Marine Science, 2024)
Estuarine sediments serve as significant reservoirs for mercury (Hg) and methylmercury(MeHg), which can also interconvert in the external environment. The release of Hg in response to human activities raises concerns about its potential ecological and human health effects. Sediment samples were collected in December 2021 from four locations (sites), and Hg cycling by measuring the concentrations of, and controls on, the spatial distribution of total Hg (THg) and methylmercury (MeHg) in high-tidal zone (HTZ) and mid-tidal zone (MTZ) sediments of a mangrove forest (MF) and oyster farm (OF) was examined in northwestern Zhanjiang Bay, including simultaneous determination of sediment particle size, oxidation-reduction potential (Eh), pH, total organic carbon (TOC), sulfide concentration (S2-), and sulfate reducing bacteria (SRB). The research results indicated that concentrations of both THg and MeHg ranged between 20.0–104.0 ng/g and 0.011–0.277 ng/g in the sediments, respectively. The highest methylation potentials within the MF and OF were in sediments located approximately 10–15 cm below the surface. MeHg in the HTZ of the OF was likely derived from exogenous inputs as Hg methylation appears limited, and the formation of MeHg depended not only on the amount of inorganic mercury available for methylation in SRB, but also on the TOC, pH, Eh and S2- content in the sediment. A risk assessment of MeHg during the anthropogenic disturbance of this estuaries conducted on individuals eating oysters demonstrated that health risks are low.